Cognitive Functional Therapy for the Management of Low Back Pain in an Adolescent Male Rower: A Case Report. - Caneiro, Joao; Ng, Leo; Burnett, A.; Campbell, Amity; O'Sullivan, P (American Physical Therapy Association, 2013)
Study Design: Case report. Background: Contemporary low back pain models propose that the experience of and responses to pain result from a complex interaction of biopsychosocial factors. This supports the need for a management approach that addresses the biological, psychological, and social components that may be related to the pain disorder. This case report demonstrates the application of, and outcomes associated with, a cognitive functional intervention that considers neurophysiological, physical, psychosocial, cognitive, and lifestyle dimensions for the management of a rower with nonspecific chronic low back pain. Case Description: An adolescent male club-level rower with nonspecific chronic low back pain was classified as having a motor control impairment with a lower lumbar compressive-loading pattern in flexion. Evaluation of this patient included ergometer rowing analysis (clinical and laboratory) before and after an 8-week intervention, and outcome measures at a 12-week follow-up. The intervention consisted of a cognitive functional approach that targeted optimization of movement behavior, providing the rower with alternative movement strategies to minimize sustained flexion loading.Outcomes: Reduced temporal summation of pain while ergometer rowing and reduced functional disability were observed preintervention to 12 weeks postintervention by changes in Roland-Morris Disability Questionnaire score (12/24 to 1/24) and the Patient-Specific Functional Scale (4/30 to 26/30), and associated improvements in lower-limb and back muscle endurance and changes in hip and spinopelvic kinematics during ergometer rowing. In particular, there was a greater use of available range of movement in the lumbar spine postintervention. Discussion: The cognitive functional intervention for this patient resulted in reduced pain and functional disability related to ergometer rowing, which was associated with a change in lumbar kinematics and improved lower-limb and back muscle endurance. The results suggest that providing the rower with greater use of his available range of movement may enhance load distribution during the drive phase of rowing.